2020
DOI: 10.3390/genes11091086
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Therapy: Experiences and Perspectives for Regenerative Medicine

Abstract: Ultrasound has emerged as a novel tool for clinical applications, particularly in the context of regenerative medicine. Due to its unique physico-mechanical properties, low-intensity ultrasound (LIUS) has been approved for accelerated fracture healing and for the treatment of established non-union, but its utility has extended beyond tissue engineering to other fields, including cell regeneration. Cells and tissues respond to acoustic ultrasound by switching on genetic repair circuits, triggering a cascade of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 125 publications
1
40
0
Order By: Relevance
“…Gross morphological analysis of stimulated s-MPs indicated that the protocol was not detrimental, as morphology was similar to control cells throughout the three-day application. However, it has also been described that LIPUS can induce apoptosis when higher intensities are applied [3,45,46] as occurs when we used 1 W/cm 2 intensity as a positive control for ultrasound stimulation. Therefore, LIPUS could be a potential tool for the treatment of some cancers [47].…”
Section: Plos Onementioning
confidence: 83%
See 1 more Smart Citation
“…Gross morphological analysis of stimulated s-MPs indicated that the protocol was not detrimental, as morphology was similar to control cells throughout the three-day application. However, it has also been described that LIPUS can induce apoptosis when higher intensities are applied [3,45,46] as occurs when we used 1 W/cm 2 intensity as a positive control for ultrasound stimulation. Therefore, LIPUS could be a potential tool for the treatment of some cancers [47].…”
Section: Plos Onementioning
confidence: 83%
“…Mechanical wave are sense by cell mechanoreceptors, that are transmembrane proteins that link with the cytoskeleton [2]. Once the mechanoreceptor receives the mechanical stimuli lead to the activation of different signaling pathways with finally rule cell fate, including quiescence, cell adhesion, proliferation, migration, differentiation, or apoptosis [3]. Hence, ultrasound, as mechanical stimuli, has the potential to regulate cell behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic LIUS has been used to enhance bone healing caused by fracture in humans ( 1 , 2 ). The effects and possible advantages of ultrasound have been a subject of increasing interest in other fields of medicine as well, including oncology, surgery, gene therapy and regenerative medicine ( 50 56 ). Therefore, genetic effects should also be considered to be a factor in these other fields.…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue injuries can be divided into open wounds and deep tissue injuries (stress, strains, sprains, and tears). De Lucas et al reviewed the application of ultrasound therapy and the underlying activation of molecular and cellular pathways leading to cellular differentiation, proliferation, migration, matrix regeneration, and its biological effects in regenerative medicine [ 38 ]. The review extensively discussed LIPUS applications in clinical studies and respective regenerative outcomes in various tissues.…”
Section: Applications Of Low-intensity Continuous Ultrasoundmentioning
confidence: 99%
“…In contrast, LICUS stimulation has both mechanical and thermal effects at the tissue and cellular level. There are numerous comprehensive reviews that have described the effectiveness of LIPUS for various medical applications [ 24 , 38 , 39 , 40 , 41 ], but to our knowledge, there is no comprehensive review summarizing the therapeutic efficacy of LICUS. In the last few decades, there have been significant developments in LICUS applications.…”
Section: Introductionmentioning
confidence: 99%